The Phenomenon Of “Euphemism Inflation” In Contemporary Political Discourse - Jabborova, Aziza Jobirovna (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article explores the phenomenon of euphemism inflation in contemporary political discourse. Traditionally, euphemisms have been viewed as linguistic tools used to ensure politeness and ethical communication by softening socially sensitive or controversial issues. However, in modern political discourse, euphemisms are increasingly used in excessive and repetitive ways, leading to a gradual dilution of meaning. The study adopts a qualitative, discourse-oriented approach and is based on general materials of contemporary political discourse. Through discourse analysis, critical discourse analysis, and linguopragmatic interpretation, the article examines how euphemism inflation affects semantic clarity, political accountability, and audience perception. The findings reveal that euphemism inflation contributes to semantic erosion, indirect management of responsibility, and normalization of controversial political actions. While euphemistic language initially aims to maintain ethical balance and reduce confrontation, its excessive use may result in ambiguity, reduced transparency, and growing public scepticism. The article argues that euphemism inflation should be treated as an independent analytical category within political discourse studies and highlights its significance for understanding modern political communication.